A Note on the Steady Flow of Newtonian Fluids with Pressure Dependent Viscosity in a Rectangular Duct - Siginer, D (Elsevier Ltd, 2016)
Unidirectional steady flow of Newtonian liquids with a pressure-dependent viscosity in a rectangular duct is considered. Governing momentum equation is reduced to a quasilinear second order elliptic partial differential equation. We give an analytical solution to the governing equation, and investigate the effect of aspect ratio and pressure coefficient on the velocity profiles numerically. © 2016 Elsevier Ltd. All rights reserved.